RELATIONSHIP OF STRESS AND ACADEMIC PERFORMANCE AMONG UNIVERSITY STUDENTS: A CASE STUDY OF GENDER COMPARISON - Hamidah Muhd Irpan; Noorazilah Ibrahim; Shahitul Badariah Sulaiman; Nurul Emyza Zahidi; Fatimah Hashim, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
A student can be stressed due to many factors such as problems with family, friends, financial, and study. Stress level also differs between male and female students. Many studies proved that stress problem has a negative impact on academic performance. As a university student, academic performance is measured by the cumulative grade point average (CGPA). Stress problem among students should be faced in a positive manner. Hence this study focuses in determining (i) the stress level among students by gender, (ii) the effect of being stressed, (iii) the relationship of stress and academic performance by gender and (iv) their ways of handling stress. Population in the study is all students in UiTM Cawangan Melaka. 145 students were selected as sample using convenience sampling. Data was collected using an online questionnaire. Descriptive and chi-square test were used to analyse data. Findings show that generally, stress is not related to academic performance. Somehow, stress caused by a problem with friends is related to academic performance for male students while stress caused by the financial problem is related to academic performance for female students Most of the students prefer having sleep, listening to music, and having food to handle stress.